Fractal Dimension (Df) Theory of Ismail’s Entropy (IE) with Potential Df Applications to Structural Engineering - A Mageed, Ismail (Journal of Intelligent Communication, 2024)
As an ultimate generalisation to several kinds of generalised entropy in the literature, a novel entropy measure, namely, Ismail’s entropy, or (IE), is presented. This article spotlights the significance of fractal dimension, through highlighting several possible applications of fractal dimension to structural engineering. In addition to several difficult open problems and the next step of inquiry, the paper ends with some concluding observations.